Finding, inheriting or borrowing? : the construction and transfer of knowledge in antiquity and the Middle Ages (Mainzer historische Kulturwissenschaften, 2019)
The creation and justification of knowledge in antiquity and the Middle Ages gives rise to several questions: How is `foreign' knowledge given authority? What are the mechanisms of legitimation? Are the ascriptions by the sources concerning the origin of knowledge as either inherited or borrowed traceable and comprehensible or artificial and unfounded? Does transferred knowledge create new concepts during the act of borrowing?To answer these questions, the volume is divided into three parts: After a section on theoretical and methodological considerations, two thematic sections deal with a special field of knowledge, i.e. on concepts of the moon and of the end of the world in fire.